Resolving trabecular metaphyseal bone profiles downstream of the growth plate adds value to bone histomorphometry in mouse models - Salmon, P. L.; Monzem, S.; Javaheri, B.; Oste, L.; Kerckhofs, G.; Pitsillides, A. A. (Frontiers in Endocrinology, 2023)
Introduction. Histomorphometry of rodent metaphyseal trabecular bone, by histology or microCT, is generally restricted to mature secondary spongiosa, excluding primary spongiosa nearest the growth plate by imposing an ‘offset’. This analyses bulk static properties of a defined segment of secondary spongiosa, usually regardless of proximity to the growth plate. Here we assess the value of trabecular morphometry that is spatially resolved according to distance ‘downstream’ of the growth plate. Pursuant to this we also investigate the validity of including mixed primary-secondary spongiosal trabecular bone, extending the analysed volume ‘upstream’ by reducing the offset. Both the addition of spatiotemporal resolution and the extension of the analysed volume have potential to enhance sensitivity of detection of trabecular changes and to resolve changes occurring at different times and locations. Method. Two experimental mouse studies of trabecular bone are used as examples of different factors influencing metaphyseal trabecular bone: ovariectomy (OVX) and pharmacological prevention of osteopenia, and limb disuse induced by sciatic neurectomy (SN). To test validity of offset imposition, we also examine the relationship between age, tibial length and primary spongiosal thickness. Results. Bone changes induced by either OVX or SN that were early, or weak and marginal, were more pronounced in the mixed primary-secondary upstream spongiosal region than in the downstream secondary spongiosa. Spatially resolved evaluation of the entire trabecular region found that significant differences between experimental and control bones remained undiminished either right up to, or to within 100 microns from the growth plate. Intriguingly, our data revealed a remarkably linear downstream profile for fractal dimension in trabecular bone, arguing for underlying homogeneity of the (re)modelling process throughout the entire metaphysis and against strict anatomical categorization into primary and secondary spongiosal regions. Finally, we find that a correlation between tibial length and primary spongiosal depth is well-conserved except in very early and late life. Conclusions. These data indicate that spatially resolved analysis of metaphyseal trabecular bone at different distances from the growth plate, and/or times since formation, adds a valuable dimension to histomorphometric analysis. They also question any rationale for rejecting primary spongiosal bone, in principle, from metaphyseal trabecular morphometry.